2011
DOI: 10.1007/s11160-011-9229-3
|View full text |Cite
|
Sign up to set email alerts
|

Life-history characteristics of eleotrid fishes of the western hemisphere, and perils of life in a vanishing environment

Abstract: The term amphidromous was coined (Myers in Copeia 1949:89-97, 1949b to describe diadromous life histories that include migrations, not associated with reproduction, that are between fresh and marine waters. This concept has facilitated evaluations of life cycles among a number of groups of fishes including some belonging to the family Eleotridae. Information was gathered on life history patterns of eleotrid fish species that have been recorded from both fresh and brackish or marine waters of the east and west … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 137 publications
(152 reference statements)
1
16
2
Order By: Relevance
“…Dormitator maculatus and Gobiomorus dormitor , which are found in rivers and estuaries of Florida, the Gulf of Mexico and the Caribbean, as well as in Brazil (Castro‐Aguirre, ; Froese & Pauly, ; Gilbert & Williams, ; Robins & Ray, ), are species adapted to major fluctuations in salinity, but have low dispersal capacity (Nordlie, ). While specimens from northern South America were not included in the present study, the analyses indicated the presence of two substantial evolutionary lineages of G. dormitor in the disjunct populations found in Veracruz (Mexico) and the Caribbean (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dormitator maculatus and Gobiomorus dormitor , which are found in rivers and estuaries of Florida, the Gulf of Mexico and the Caribbean, as well as in Brazil (Castro‐Aguirre, ; Froese & Pauly, ; Gilbert & Williams, ; Robins & Ray, ), are species adapted to major fluctuations in salinity, but have low dispersal capacity (Nordlie, ). While specimens from northern South America were not included in the present study, the analyses indicated the presence of two substantial evolutionary lineages of G. dormitor in the disjunct populations found in Veracruz (Mexico) and the Caribbean (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…used to separate lineages (Hebert et al, 2003). The pairwise genetic distance matrix ( Robins & Ray, 1986), are species adapted to major fluctuations in salinity, but have low dispersal capacity (Nordlie, 2012).…”
Section: Dna Barcodingmentioning
confidence: 99%
See 2 more Smart Citations
“…The bigmouth sleeper [ Gobiomorus dormitor (Lacepède, 1800)] is an eleotrid fish inhabiting tropical and subtropical coastal freshwater and brackish environments in the Caribbean, south‐eastern Florida, southern Texas, and the Atlantic slope of Central and northern South America (Lindquist, ; Gilmore, ). Gobiomorus dormitor is commonly catadromous or amphidromous (Darnell, ; Winemiller & Ponwith, ; Adelsberger, ; Nordlie, ), using saltwater regions during egg laying or larval development, but is also known to reproduce in some landlocked lakes and reservoirs (Darnell, ; McKaye, Weiland & Lim, ; Holmquist, Schmidt‐Gengenbach & Yoshioka, ; Bedarf et al ., ; Bacheler, Neal & Noble, ). In coastal streams and lakes (its ancestral environment), G. dormitor is a benthic, ambush predator, feeding primarily on fish and large invertebrates (McKaye, Weiland & Lim, ; Winemiller & Ponwith, ; Bedarf et al ., ; Bacheler, Neal & Noble, ).…”
Section: Introductionmentioning
confidence: 99%